Measurements and Simulations of Neutron Emission Versus Deuterium Filling Pressure in Plasma Focus Device PF-24 - Łukasz, Marciniak; Mohamad, Akel; Agnieszka, Kulińsk; Scholz, Marek; Hans-Joachim, Kunze; Lee, Sing; Saw, Sor Heoh (Springer, 2018)
A series of experiments were carried out using the middle energy (dense) plasma focus device PF-24 with deuterium as a working gas under pressure in a range between 2 and 5 mbar for 17 kV of charging voltage. The relationship between these operating deuterium pressures in reference to the total neutron yield (Yn) was estimated. The 5-phase Lee code was used to simulate the measured discharge current and neutron yield (Yn) using a phenomenological beam-target neutron generating mechanism, which was incorporated in the model. Comparison of the Yn versus pressure using fitted model parameters was made at each point of pressure. The good agreement between measured and computed Yn values was achieved for discharges with lower neutron emission. The measured Yn (below 2.6 × 109 n/discharge—the median value) has been reproducible by the model for 73% of simulated discharges, while above the median value its prediction were incorrect. The kinetic plasma parameters which were measured and computed using the Lee code for different pressures are: the time to a current sheath collapse (tc), the average axial current sheath velocity (vz) and the so called velocity factor (RF). Good agreement was found in the whole range of deuterium pressures between the computed and measured results for these kinematic quantities. Presented findings in this work suggest that the character of neutron emission is more complex than it would seem from classical interpretation of neutron production based on a beam-target model.